Synthesis and crystal structure of anti-10-(4-cyanophenyl)-10,11,22,23-tetrahydro-9H,21H-5,8:15,12-bis(metheno)[1,5,11]triazacyclohexadecino[1,16-a:5,6-a′]diindole dichloromethane monosolvate - Koji Kubono; Keita Tani; Yukiyasu Kashiwagi (Acta Crystallographica Section E: Crystallographic Communications)
The asymmetric unit of the title compound is composed of one host molecule, anti-4-(19H,59H-3-aza-1,5(3,9)-dicarbazolacyclooctaphane-3-yl)benzonitrile and one dichloromethane solvate molecule, C36H28N4·CH2Cl2. The host molecule possesses a planar chirality but crystallizes as a racemate in the space group P21/c. It adopts an anti-configuration, in which two carbazole rings are partially overlapped with a parallel orientation. The two carbazole ring systems are slightly bent, and the C atoms at the 3- and 1-positions show the largest deviations from the mean planes. The dihedral angle between two carbazole rings is 9.42 (3)°, forming an intramolecular parallel π–π interaction [Cg...Cg = 3.2755 (9) Å]. In the crystal, the molecules are linked via host–host and host–guest C—H...π interactions, forming chain structures along the a-axis direction. The molecules are linked into a ribbon structure along the c-axis direction by further C—H...π interactions. As a result, The molecules are cross-linked by C—H...π interactions into a three-dimensional network.